Induction of lignin and pathogenesis related proteins in dragon fruit plants in response to submicron chitosan dispersions - Ali, Asgar; Zahid, Noosheen; Manickam, Sivakumar; Siddiqui, Yasmeen; Alderson, Peter G.; Maqbool, Mehdi (Elsevier, 2014)
Chitosan is capable of triggering the induction of defence responses of the plants. This study was carried out to investigate in vitro and in vivo antifungal activity of submicron chitosan dispersions and also to determine the mechanism of induced resistance in dragon fruit plants by strengthening of cell wall and production of pathogenesis related proteins. Highest inhibition in radial mycelial growth (90.2%) was obtained by 600 nm droplet size at 1.0% chitosan concentration. None of the emulsifiers showed any antifungal effect during in vitro studies. Field studies showed the reduction of 22% disease incidence and 66% disease severity in anthracnose on dragon fruit plants treated with 600 nm droplet size as compared to control plants after one month of assessment. Lignin contents in cell wall of dragon fruit plants increased 2 folds in plants treated with 1.0% chitosan at 600 nm droplet size while 11 and 10 folds increase in β-1,3-glucanase and chitinase activity, respectively was also recorded in the plants inoculated with Colletotrichum gloeosporioides. The accumulation of lignin and higher level activity of pathogenesis related proteins in response to submicron chitosan dispersions may bolster in mounting effective resistance against the devastating disease of anthracnose.